A new single nucleotide polymorphism in the rabbit (Oryctolagus cuniculus) myostatin (MSTN) gene is associated with carcass composition traits. (2nd May 2014) - Sternstein, Ina; Reissmann, Monika; Maj, Dorota; Bieniek, Josef; Brockmann, Gudrun A.
Summary This study aimed at the identification of genetic variations in the myostatin (MSTN) gene and testing their effects on carcass quality traits. We comparatively sequenced Giant Grey (GG) and New Zealand White (NZW) rabbits that were founders of a cross‐bred population. Alignment of our sequence data with the GenBank sequence of the rabbit MSTN gene (Ensembl Gene ID ENSOCUG00000012663) identified three single nucleotide polymorphisms (SNPs). The two novel SNPs (c.−125T>C, c.373+234G>A) and one known SNP (c.747+34C>T) were subsequently analysed for linkage with carcass composition traits in 363 F2 animals of the cross GG × NZW. Significant linkage was found between c.373+234G>A and nine carcass composition traits (P < 0.05). No significant effects were found for c.−125T>C and c.747+34C>T. Because the linked SNP is located in intron 1 and no genetic variation was found in the coding region, further investigations are necessary to understand the functional effect of the c.373+234G>A variant on the variability of the traits.